2015
DOI: 10.1126/science.aaa5333
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microstructure on local carrier lifetime in perovskite solar cells

Abstract: The remarkable performance of hybrid perovskite photovoltaics is attributed to their long carrier lifetimes and high photoluminescence (PL) efficiencies. High-quality films are associated with slower PL decays, and it has been claimed that grain boundaries have a negligible impact on performance. We used confocal fluorescence microscopy correlated with scanning electron microscopy to spatially resolve the PL decay dynamics from films of nonstoichiometric organic-inorganic perovskites, CH3NH3PbI3(Cl). The PL in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

126
1,917
6
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,988 publications
(2,058 citation statements)
references
References 40 publications
126
1,917
6
9
Order By: Relevance
“…Our results reported here on both I‐ and Br‐based perovskites that do not contain any Cl suggest that the observation might be more general and may not originate from fluctuations of elemental composition. It has been found that the presence of chloride aids nucleation,15 which would allow to reconcile the previous report35 with our findings and supports our more general interpretation that high‐intensity regions on perovskites are connected with higher crystallinity. The slightly red‐shifted and broader emission in the low PL regions in both I‐ and Br‐based films, which is consistent with the effect observed in ref 35.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Our results reported here on both I‐ and Br‐based perovskites that do not contain any Cl suggest that the observation might be more general and may not originate from fluctuations of elemental composition. It has been found that the presence of chloride aids nucleation,15 which would allow to reconcile the previous report35 with our findings and supports our more general interpretation that high‐intensity regions on perovskites are connected with higher crystallinity. The slightly red‐shifted and broader emission in the low PL regions in both I‐ and Br‐based films, which is consistent with the effect observed in ref 35.…”
supporting
confidence: 93%
“…These radiative recombination centers show consistently narrower PL peaks, which can be attributed to lower energetic disorder. We have very recently become aware of a similar observation of spatially inhomogeneous photoluminescent properties in films of CH 3 NH 3 PbI 3 (Cl), which are interpreted in terms of spatial fluctuations of the iodine:chlorine ratio 35. Our results reported here on both I‐ and Br‐based perovskites that do not contain any Cl suggest that the observation might be more general and may not originate from fluctuations of elemental composition.…”
supporting
confidence: 65%
“…[11][12][13] Perovskite monocrystalline (i.e. single crystal) films, which are free of grain boundaries, can achieve the upper bounds of lifetimes and diffusion lengths for all carriers homogeneously across the perovskite layer, [11] and thus enable the engineering of PSCs with a single junction to efficiently separate and collect photocarriers. [14] A simpler device architecture based on a monocrystalline film may provide a potential solution for overcoming the challenges in the development of PSCs.…”
mentioning
confidence: 99%
“…[11] The promising efficiencies we have achieved in the Schottky-junction based device structure were obtained primarily by optimizing the thickness of the perovskite layer. The performance of solar cells, however, is well known to be sensitive to the interface properties.…”
mentioning
confidence: 99%
“…Therefore, it is necessary to passivate the trap states of perovskite. Some n‐type organic semiconductors containing nitrogen or sulfur atoms are used to passivate the perovskite defects in inverted PSCs,11 since nitrogen or sulfur atoms can provide lone pair electrons to form coordination bonding with under‐coordinated Pb atoms. However, to our knowledge, there have been no reports for p‐type organic semiconductors to serve as the interlayer at perovskite/HTL interface in conventional PSCs.…”
Section: Introductionmentioning
confidence: 99%